Meningkatkan Hasil Belajar Matematika Siswa Dengan Memaksimalkan Penggunaan Media Pembelajaran Matematika - La Ode Sirad; Herlina; Arnawati (Arden Jaya Publisher, 2021)
This research is motivated by the desire to know the improvement of student learning outcomes by maximizing the use of mathematics learning media with three-dimensional real objects media. Less interesting learning without the support of effective media and on average students do not like mathematics, causing students' math scores to be low. The low learning outcomes are more visible, especially in abstract subjects that require the use of learning media. The problem studied is